Adulthood rites - Butler, Octavia E (Butler, Octavia E. Xenogenesis, 1997)
"Nuclear war had nearly destroyed mankind when the Oankali came to the rescue, saving humanity -- but at a price. The Oankali survive by mixing their DNA with that of other species, and now on Earth they have permitted no child to be born without an Oankali parent. The first true hybrid is a boy named Akin -- son of Lilith Iyapo -- and to the naked eye he looks human, for now. He is born with extraordinary sensory powers, understanding speech at birth, speaking in sentences at two months old, and soon developing the ability to see at the molecular level. More powerful than any human or Oankali, he will be the architect of both races' intergalactic future. But before he can carry this new species into the stars, Akin must decide which unlucky souls will stay behind."--Publisher description.